Is dissociation predicting the efficacy of psychological therapies for PTSD?: Results from a randomized controlled trial comparing Dialectical Behavior Therapy for PTSD (DBT-PTSD) and Cognitive Processing Therapy (CPT) - Kleindienst, Nikolaus; Steil, Regina; Priebe, Kathlen; Müller-Engelmann, Meike; Lindauer, Petra; Krause-Utz, Annegret; Friedmann, Franziska; Schmahl, Christian; Enning, Frank; Bohus, Martin (Psychological medicine, 2025)
BackgroundNeuropsychological evidence suggests that dissociation might disturb emotional learning, which is a fundamental mechanism of psychotherapy. However, a recent meta-analysis on the impact of dissociation on treatment outcomes in psychotherapy trials for posttraumatic stress disorder (PTSD) reported inconsistent results and concluded that further high-quality clinical trials are needed to test whether dissociation affects the efficacy of psychotherapies. We had two main aims: First, to test whether the efficacy of two evidence-based psychotherapies for individuals with trauma-related PTSD is affected by the level of pretreatment dissociation. Second, we investigated whether a significant reduction in dissociation at an early stage of treatment is beneficial for subsequent efficacy.MethodsThe potential impact of dissociation on efficacy was studied in 193 women with PTSD related to childhood abuse who were randomized to dialectical behavior therapy for PTSD (DBT-PTSD) or cognitive processing therapy (CPT). Efficacy was operationalized as a change in the Clinician-Administered PTSD Scale (CAPS). Dissociation was assessed with the Dissociation Tension Scale (DSS). The analyses accounted for major confounders (in particular initial PTSD severity).ResultsTwo main findings emerged from this study. First, baseline dissociation was a negative predictor for treatment efficacy. Second, a significant drop in dissociation at the initial stages of treatment was beneficial for subsequent efficacy.ConclusionsDissociation likely reduces the efficacy of trauma-focused therapies. Accordingly, successful reduction of dissociation at an early stage of treatment assists the efficacy of trauma-focused psychotherapies.